A Comparison of Functional Endothelial Changes between Phacoemulsification with PCIOL and Manual Small Incision Cataract Surgery with PCIOL - Hasan, Mohammad Mahbubul; Kajmina, Natasha; Begum, Hasiba (Mugda Medical College Journal, 2024)
Intraocular surgery e.g., cataract surgery with PCIOL implantation is one of the leading causes of corneal endothelial injury and change in the functionality of the cornea. This observational study was conducted in the Department of Ophthalmology of Combined Military Hospital (CMH), Dhaka Cantonment, Dhaka, Bangladesh, between January and July of 2016, to assess and compare functional changes in cornea (i.e., endothelial thickness) after phacoemulsification with posterior chamber intraocular lens (PCIOL) implantation and manual small incision cataract surgery (MSICS) with PCIOL implantation. A total of 80 patients of age-related cataract were randomly selected based on inclusion and exclusion criteria. All patients underwent complete ophthalmic evaluation pre- and post-operatively (at day 1, after 1 week and 3 months) specifically for observation of the endothelial changes in cornea. Specular microscopy was done to assess corneal endothelial change. The mean central corneal thickness was increased at day 1 (564.71±22.45μ vs. 555.10±40.57μ), after 1 week (539.43±22.16μ vs. 535.08±38.87μ) and 3 months (523.49±21.29μ vs. 520.05±33.68μ) after phacoemulsification and MSICS from their preoperative value (508.72±23.96μ vs. 503.62±32.06μ) respectively. However, the differences were not statistically significant between two groups (P>0.05). The mean percentage of central corneal thickness change at day1, after 1 week and after 3 months following cataract surgery were found 11.01±6.30% and 10.22±26.54% at day 1, 6.04±7.52% and 6.25±21.24% after 1 week, 2.90±11.14% and 3.26±5.05% after 3 months in phacoemulsification and MSICS cases respectively. However, no statistically significant difference was observed in percentage of central corneal thickness change of both groups (P>0.05). To summarize, an increased central corneal thickness was observed after phacoemulsification and SICS from their preoperative values. Mugda Med Coll J. 2024; 7(1): 14-18